A Novel Control Strategy for Compensation of Voltage Quality Problem in AC Drives - Syed Suraya; P. Sujatha Sujatha; Bharat Kumar P (Institute of Advanced Engineering and Science, 2018)
This paper presents a novel control strategy for the compensation of voltage quality issues in power system networks with AC drives. Voltage quality is one of the key parameter for power engineers and to deliver the power with good quality should be given at most priority. Voltage quality mitigation in power system network is done by employing dynamic voltage restorer (DVR). DVR consists of power switches and power switches are to be controlled. DVR in this paper is controlled using a novel control strategy. A novel control strategy can effectively control DVR by improving voltage quality reducing the adverse effects of voltage sag and voltage swell in power system networks. The paper presents the DVR controlled with novel control strategy for electrical machine (induction motor) drive load application.